2015
DOI: 10.1128/ec.00083-15
|View full text |Cite
|
Sign up to set email alerts
|

The Centriole Cartwheel Protein SAS-6 in Trypanosoma brucei Is Required for Probasal Body Biogenesis and Flagellum Assembly

Abstract: The centriole in eukaryotes functions as the cell's microtubule-organizing center (MTOC) to nucleate spindle assembly, and its biogenesis requires an evolutionarily conserved protein, SAS-6, which assembles the centriole cartwheel. Trypanosoma brucei, an early branching protozoan, possesses the basal body as its MTOC to nucleate flagellum biogenesis. However, little is known about the components of the basal body and their roles in basal body biogenesis and flagellum assembly. Here, we report that the T. bruce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 48 publications
(72 reference statements)
1
58
0
Order By: Relevance
“…In addition to mediating flagellum-cell body attachment, the FAZ filament also defines the cytokinesis cleavage plane (11,12), with the distal tip of the new FAZ filament marking the site of cytokinesis initiation (18 -20). Moreover, during the cell cycle in the procyclic form, the elongation of the FAZ filament positions the newly assembled basal body toward the cell posterior (21), which is crucial for organelle segregation and cell division (10,(22)(23)(24)(25).Trypanosomatids, a group of kinetoplastid parasites consisting of T. brucei, Trypanosoma cruzi, and Leishmania spp., appear in a variety of different morphological forms during their life cycle and are distinguished by the relative position of the kinetoplast (mitochondrial DNA) and the nucleus and by the position, length, and cell body attachment of the flagellum (26). In the tsetse fly vector, T. brucei differentiates from the trypomastigote form to the epimastigote form, which undergoes asymmetrical cell division to produce a long epimastigote cell and a short epimastigote cell (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to mediating flagellum-cell body attachment, the FAZ filament also defines the cytokinesis cleavage plane (11,12), with the distal tip of the new FAZ filament marking the site of cytokinesis initiation (18 -20). Moreover, during the cell cycle in the procyclic form, the elongation of the FAZ filament positions the newly assembled basal body toward the cell posterior (21), which is crucial for organelle segregation and cell division (10,(22)(23)(24)(25).Trypanosomatids, a group of kinetoplastid parasites consisting of T. brucei, Trypanosoma cruzi, and Leishmania spp., appear in a variety of different morphological forms during their life cycle and are distinguished by the relative position of the kinetoplast (mitochondrial DNA) and the nucleus and by the position, length, and cell body attachment of the flagellum (26). In the tsetse fly vector, T. brucei differentiates from the trypomastigote form to the epimastigote form, which undergoes asymmetrical cell division to produce a long epimastigote cell and a short epimastigote cell (26).…”
mentioning
confidence: 99%
“…In addition to mediating flagellum-cell body attachment, the FAZ filament also defines the cytokinesis cleavage plane (11,12), with the distal tip of the new FAZ filament marking the site of cytokinesis initiation (18 -20). Moreover, during the cell cycle in the procyclic form, the elongation of the FAZ filament positions the newly assembled basal body toward the cell posterior (21), which is crucial for organelle segregation and cell division (10,(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…The results showed that 3HA-SPBB1 was localized to the basal body as verified by co-localization with TbSAS-6, the basal body cartwheel protein in both the mature basal body and the probasal body (25) (Fig. 2A).…”
Section: Spbb1 Co-localizes With Tbplk In the Basal Body During Earlymentioning
confidence: 69%
“…Fixed cells were then rehydrated with PBS and incubated in blocking buffer (1% BSA and 0.1% Triton X-100 in PBS) for 1 h at room temperature. Cells were then incubated with the primary antibody diluted in PBS containing 1% BSA at room temperature for 1 h. The following primary antibodies were used: FITC-conjugated anti-HA mAb (1:400 dilution, Sigma-Aldrich), anti-protein A pAb (1: 400 dilution, SigmaAldrich), anti-TbPLK pAb (1:1,000 dilution), L3B2 (1:20 dilution) (22), YL 1/2 mAb (1:1,000 dilution) (23), 20H5 (anti-Centrin mAb, 1:400 dilution) (24), PS54 (anti-phospho-Ser-54 of TbCentrin2, 1: 30,000 dilution) (16), and anti-TbSAS-6 pAb (1:1,000 dilution) (25). After three washes with wash buffer (0.1% Triton X-100 in PBS), cells were incubated with FITCconjugated or Cy3-conjugated secondary antibody at room temperature for another hour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation